(untitled) (Indian Journal of Public Health Research & Development, 2022)
This study investigates the linkages between health and economic development focusing the seven South Asian (SA) countries for the period of 2000-15. Firstly, a situation analysis of major health indicators indicates that SA countries are advancing well in life expectancy, mortality and fertility rate while the burden of diseases is shifting from infectious diseases to noncommunicable diseases. The study finds that private sources mainly out of pocket health expenditure dominates the total spending on health care. Using the linear regression method, the research also finds that health expenditure growth is positively correlated with Nominal GDP growth in this region. This study also discusses the health facility situations and finds that health workforce deficiency challenge is critical in SA countries. This research also recommends that closing gaps in primary care, strengthening accessibility of health care and making progress in health determinants are necessary to expand Universal Health Coverage (UHC) in the SA region. Finally, the study has listed the major policy interventions in the SA countries and highlighted a couple of areas to be addressed for health sector advancement.